Larvae of longhorned beetles (Coleoptera; Cerambycidae) have evolved a diverse and phylogenetically conserved array of plant cell wall degrading enzymes. (11th May 2021) - Shin, Na Ra; Shin, Seunggwan; Okamura, Yu; Kirsch, Roy; Lombard, Vincent; Svacha, Petr; Denux, Olivier; Augustin, Sylvie; Henrissat, Bernard; McKenna, Duane D.; Pauchet, Yannick
Abstract: Longhorned beetles (Cerambycidae) are the most diverse group of predominantly wood‐feeding (xylophagous) insects on Earth. Larvae of most species feed within tissues of plants made up of large amounts of plant cell wall (PCW), which is notoriously difficult to digest. To efficiently access nutrients from their food source, cerambycid larvae have to deconstruct PCW polysaccharides – such as cellulose, hemicelluloses and pectin – requiring them to possess a diversity of plant cell wall degrading enzymes (PCWDEs) in their digestive tract. Genomic data for Cerambycidae are mostly limited to notorious forest pests and are lacking for most of the taxonomic groups. Consequently, our understanding of the distribution and evolution of cerambycid PCWDEs is quite limited. We addressed the numbers, kinds and evolution of cerambycid PCWDEs by surveying larval midgut transcriptomes from 23 species representing six of the eight recognized subfamilies of Cerambycidae and each with very diverse host types (i.e., gymnosperms, angiosperms, xylem, phloem, fresh or dead plant tissues). Using these data, we identified 340 new putative PCWDEs belonging to ten carbohydrate active enzyme families, including two gene families (GH7 and GH53) not previously reported from insects. The remarkably wide range of PCWDEs expressed by Cerambycidae should allow them to break down most PCW polysaccharides. Moreover, the observed distribution of PCWDEs encoded in cerambycid genomes agreed more with phylogenetic relationship of the species studied than with the taxonomic origin or quality of the host plant tissues. Abstract : We addressed the numbers, kinds and evolution of cerambycid plant cell wall degrading enzymes (PCWDEs) by surveying larval midgut transcriptomes from 23 species representing six of the eight recognized subfamilies of Cerambycidae. We identified 340 new putative PCWDEs belonging to ten carbohydrate active enzyme families, including two gene families (GH7 and GH53) not previously reported from insects. The observed distribution of PCWDEs encoded in cerambycid genomes agreed more with phylogenetic relationship of the species studied than with the taxonomic origin or quality of the host plant tissues.